ESG Transformation in the Largest Emerging Capital Market of China. A Literature Review - Wu, Yanfei (Journal of Corporate Finance Research / Корпоративные Финансы | ISSN: 2073-0438, 2023)
The paper provides a scholarly examination of academic studies of the ESG landscape in China through a systematic literature review with a major focus on the nature and intensity of regulatory guidelines and policies. While many studies indicate positive effects of Chinese ESG policies on corporate ESG performance and investment, they primarily focus on environmental aspects. This analysis of China’s ESG rating system exposes relationships between ESG ratings, corporate performance, financing costs, including both debt and equity financing. The research on equity financing costs is inconsistent and limited in scope, indicating the need for additional investigation. Of the factors influencing ESG, the past year has seen a surge in research on the topic of digital transformation and ESG performance. Most studies demonstrate that digital transformation contributes to ESG performance, and a few suggest that digital transformation positively moderates the effect of ESG performance on firm value enhancement. This review discusses the growth of ESG investment in China, focusing on pension funds, commercial banks, and ESG funds, as well as investor preferences. Despite the growing role of ESG in investment decisions, extant research is largely theoretical, underscoring the need for more empirical and quantitative studies. The research identifies gaps in studies devoted to ESG investment, including the need for comprehensive studies on the impact of ESG across various insurance types and industries, and the development of effective ESG quality assessment methods. This review is among the first academic resources summarizing and integrating various studies, and highlighting areas for future ESG research in China.